CAPITAL STRUCTURE AND BANK PERFORMANCE - Arie Widyastuti; Ratna Komara; Layyinaturrobaniyah Layyinaturrobaniyah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
The decision of how firms finance their investments is among the prominent researchers in the area of corporate finance. The capital structure of banks, however, still relatively under-explored. Banking is one type of industry that employs a high level of leverage in creating companies’ value since its operating profits come from lending and borrowing activities. This research aims to analyse the effect of the mix of capital structure on financial performance of commercial banks in Indonesia. We use annual data for the period 2009 – 2017 that are extracted from the audited financial statement. The data is then analysed to find relationship on the use of leverage to the firms’ performance. Our study finds strong evidence that short term loan significantly has positive influence on profitability of banks through Return on Equity (ROE), which indicates that deposit is considered as the cheapest source of funding. However, banks should carefully maintain their liquidity risk to ensure the availability of funds to pay for withdrawals obligation. We also found that the use of long-term debt and the use of equity, in general, do not have a significant effect on firm value, which indicates that, in terms of long-term financing, profitability and firm value are insensitive to capital structure.